KEADILAN PROSEDURAL DAN SUBSTANTIF DALAM AKAD MUDHARABAH - Nasrul Amanu (CV JK Riset Publishing Group, 2025)
This study examines the application of procedural and substantive justice in the mudharabah contract using a normative juridical approach based on classical Islamic legal texts, contemporary Islamic finance regulations, and empirical findings from previous studies. The results indicate that procedural justice in mudharabah remains insufficient, particularly in terms of information transparency, agreement mechanisms, and balanced bargaining positions between the capital provider (shahib al-māl) and the entrepreneur (mudhārib). Substantive justice is similarly challenged, especially regarding profit-sharing arrangements and risk distribution, both of which often fail to reflect the ideal structure of mudharabah as a genuine profit-and-loss sharing contract. Current institutional practices tend toward risk-averse financing models that deviate from the foundational principle of risk-sharing. This study emphasizes the need to reconstruct a justice-based mudharabah model through strengthened procedural standards, regulatory alignment, and the development of financing products that accurately reflect Islamic normative values. The findings contribute to improving the fairness, accountability, and maqāṣid-driven orientation of Islamic financial practices.